Pertimbangan Fluktuasi Populasi dalam Perhitungan Efikasi Pestisida - Edhi Martono (Universitas Gadjah Mada, 1999)
Efficacy trials are carried out to secure registration and distribution permit for pesticides in a given country. In Indonesia, the protocol exclusively relies on the statistical difference between treatments and check plots, with little regard to before-treatment population. The efficacy criterion and its defined formulas with more attention to population changes are available, and should be applied to increase the efficacy’s accuracy.